(untitled) (Research, Society and Development, 2021)
This article aims to analyze the potential of the Virtual Learning Object (VLE) Stellarium, in the final years of elementary school, regarding the teaching of basic concepts of astronomy, in the discipline of science, taking into account the limitations in science teaching. The article is a literature review, which develops a reflection on what researchers reiterate about the consequences that the lack of contextualization in science teaching has caused in the basic education of young people, presenting the popularization of science teaching, through the approach of basic concepts of astronomy that are related to the Common National Curricular Base (BNCC), as a valuable strategy to overcome this obstacle, among others. In addition, it reports the challenges of science teaching today, involving the lack of resources, conceptual errors in textbooks, and the academic training of science teachers. Thus, the inclusion of astronomy in science teaching involves motivational aspects and covers various areas of knowledge, besides having significant popularity through the advancement of scientific dissemination in the media. Given the limitations of space and teaching materials, Stellarium has resources that enhance and enable Astronomy topics in formal education. In addition, it allows the teacher to present to students several astronomical phenomena, which is important in the absence of telescopes, lunettes, binoculars, or even in the lack of space for the development of activities, awakening students to scientific literacy.